Empowering Educators Through the Transformational Teacher Program: Enhancing Students' Religious Practices - Muhamad Mansur; Fahrurrozi Fahrurrozi; Mohammad Iwan Fitriani; Yusuf Yusuf (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the effect of the Transformational Teacher Program on students' religious practices aimed at strengthening moral and ethical values and fostering appreciation for diversity. The research addresses concerns over declining student morals, ethics, and engagement with religious activities in junior high schools in Central Lombok Regency. A quantitative research design was employed, utilizing a survey method. Data were collected from 426 junior high school students through a structured questionnaire. SmartPLS version 4.0 was used for data analysis, applying factor analysis to examine the influence of independent variables on dependent variables. The results reveal that the Transformational Teacher Program significantly affects students’ religious practices (p 0.05; t 1.96), accounting for 10.7% of the variance. As role models, teachers were found to play a crucial role in promoting religious and moral values, reinforcing social solidarity, strengthening collective memory, fostering unity, and creating environments supportive of religious engagement. In conclusion, the Transformational Teacher Program positively influences the religious practices of junior high school students, contributing to the development of students' religious character, enhancing social bonds, and promoting consistent religious behaviour in daily life.